Echocardiographic Assessment of Diastolic Function in Children with Incident Systemic Lupus Erythematosus - Chang, JC (Pediatr Cardiol, 2019)
BACKGROUND: The timing and etiology of diastolic impairment in pediatric-onset systemic lupus erythematosus (SLE) are poorly understood. We compared echocardiographic metrics of left ventricular diastolic function in children at SLE diagnosis to controls and identified factors associated with diastolic indices. METHODS: Echocardiograms of children aged 5–18 years within 1 year of SLE diagnosis and age-/sex-matched controls were retrospectively read by blinded cardiologists. Clinical characteristics were abstracted separately. Z-scores for diastolic indices (E/A, e’, E/e’, and isovolumetric relaxation time (IVRT)) were calculated using published normative data and study controls, and compared using linear mixed-effects models adjusted for blood pressure. Pericardial effusions and valvular disease were also evaluated. Linear regression was used to identify factors associated with diastolic measures. RESULTS: 85 children with incident SLE had echocardiograms performed a median of 6 days after diagnosis (interquartile range (IQR) 1–70). Prior cumulative prednisone exposure was minimal (median 60 mg, IQR 0–1652). SLE cases had lower E/A, lower e’, higher E/e’, and longer IVRT compared to controls. Though none met criteria for Grade I diastolic dysfunction, Z-scores for e’, E/e’ and IVRT were abnormal in 30%, 25%, and 6% of SLE cases, respectively. Greater disease activity was associated with lower septal e’ (p<0.01), higher E/e’ (p=0.02), and longer IVRT (p<0.01). CONCLUSION: Children with incident SLE have worse diastolic indices at diagnosis compared to peers without SLE, independent of blood pressure and prior to significant prednisone exposure. Longitudinal studies will determine whether diastolic dysfunction develops in this population over time.